2022
DOI: 10.3390/healthcare10030506
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a Source of Patient Information for Meningiomas: A Content Quality and Audience Engagement Analysis

Abstract: YouTube (YT) has become a popular health information reservoir. In this study, we aimed to evaluate the content and quality of YT videos as a source of patient information for meningiomas. A YT search was conducted for the following terms: “meningioma”, “meningiomas”, “meningeal tumor”, and “psammoma”. A total of 119 videos were examined by five independent raters, using validated quality criteria, including the Quality Criteria for Consumer Health Information (DISCERN), the Journal of the American Medical Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a study conducted by Aydin and Akyol investigating the quality of information available on YouTube TM videos pertaining to thyroid cancer, the average video length was reported as 12.8 minutes [ 16 ]. In another study by Krakowiak et al, evaluating YouTube TM as a source of patient information for meningiomas, the mean video length was 18.89 minutes [ 17 ]. Gonen et al found the mean video length as 7.27 minutes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Aydin and Akyol investigating the quality of information available on YouTube TM videos pertaining to thyroid cancer, the average video length was reported as 12.8 minutes [ 16 ]. In another study by Krakowiak et al, evaluating YouTube TM as a source of patient information for meningiomas, the mean video length was 18.89 minutes [ 17 ]. Gonen et al found the mean video length as 7.27 minutes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kuru and Erken, the time since video uploading was reported as 2288.1 days [ 19 ]. Krakowiak et al reported the time since uploading as 1688.71 days [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krakowiak et al [ 12 ] checked whether information on meningiomas on the Internet is qualitative. Based on the DISCERN form, it was concluded that the information contained in the videos on meningiomas presented on YouTube is of poor quality.…”
Section: Discussionmentioning
confidence: 99%